Hijau dan Halal: Menyelaraskan Prinsip Syariah dan Keberlanjutan Ekologis - Mohammad Muafi Himam; Fakih Abdul Azis (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study investigates the integral role of government, religious scholars, and society in promoting ecological sustainability that supports Islamic economics in Indonesia. Using a qualitative analysis approach, this study investigates how policies, religious initiatives, and community participation can collaborate to achieve environmental sustainability goals that are in line with Islamic principles. The focus of the study includes examining government policies that support sustainable resource use, the role of religious scholars in educating and mobilizing Muslims on sustainable practices, and community contributions to ecological initiatives. The results show that this intersectoral collaboration is not only essential for environmental conservation but also for the implementation of a sustainable Islamic economy that emphasizes justice, sustainability, and public welfare.